Modeling Intra‐ and Interannual Variability of BVOC Emissions From Maize, Oil‐Seed Rape, and Ryegrass. (17th March 2022) - Havermann, Felix; Ghirardo, Andrea; Schnitzler, Jörg‐Peter; Nendel, Claas; Hoffmann, Mathias; Kraus, David; Grote, Rüdiger
Abstract: Air chemistry is affected by the emission of biogenic volatile organic compounds (BVOCs), which originate from almost all plants in varying qualities and quantities. They also vary widely among different crops, an aspect that has been largely neglected in emission inventories. In particular, bioenergy‐related species can emit mixtures of highly reactive compounds that have received little attention so far. For such species, long‐term field observations of BVOC exchange from relevant crops covering different phenological phases are scarcely available. Therefore, we measured and modeled the emission of three prominent European bioenergy crops (maize, ryegrass, and oil‐seed rape) for full rotations in north‐eastern Germany. Using a proton transfer reaction–mass spectrometer combined with automatically moving large canopy chambers, we were able to quantify the characteristic seasonal BVOC flux dynamics of each crop species. The measured BVOC fluxes were used to parameterize and evaluate the BVOC emission module (JJv) of the physiology‐oriented LandscapeDNDC model, which was enhanced to cover de novo emissions as well as those from plant storage pools. Parameters are defined for each compound individually. The model is used for simulating total compound‐specific reactivity over several years and also to evaluate the importance of these emissions for air chemistry. We can demonstrate substantial differences between the investigated crops with oil‐seed rape having 37‐fold higher total annual emissions than maize. However, due to a higher chemical reactivity of the emitted blend in maize, potential impacts on atmospheric OH‐chemistry are only 6‐fold higher. Plain Language Summary: For evaluating the air quality, it is important to know what kind of chemical compounds are emitted from plants into the atmosphere. Such emissions vary widely by plant type and species, including agricultural crops. These differences have not been sufficiently accounted for because long‐term field observations from relevant crops are scarcely available. Therefore, we measured and modeled the emission of three prominent European crops (maize, ryegrass, and oil‐seed rape) for full rotations in north‐eastern Germany. Using the measurements for parametrization, we simulated each measured compound individually and also evaluated the importance of these emissions for air chemistry. We can now demonstrate substantial differences between the investigated crops. For example, on an annual basis, oil‐seed rape emitted 37‐fold more overall emissions than maize, but since the emitted compounds are less reactive, its effect on air chemistry is only 6‐fold higher. Key Points: Emissions differ greatly between crop species in pattern and strength and also vary with weather conditions and phenological development Potential impacts on air chemistry vary strongly with species and depend on compound reactivity in addition to source strength of emissions Data suggest that models should better consider growth developmental stages in order to better represent the seasonality of crop emissions